Kago, Kastom and Kalja: The Study of Indigenous Movements in Melanesia Today - Marcellin Abong (pacific-credo Publications, 2013)
This volume, bringing together six ethnographic papers and an epilogue first presented at ASAO sessions in 2009 (Santa Cruz) and 2010 (Alexandria), includes a wealth of ethnographic and historical information on a topic of enduring interest in Pacific studies and anthropology: cargo cults. These fascinating social phenomena undoubtedly have ongoing relevance for ethnographies of Melanesia. In this collection of papers, we learn about the history of the concept itself as well as how contemporary movements articulate world views, political awareness, material desires and even criticism of the now globalized concept of cargo cult itself. The chapters offer remarkable stories of cult activities and interesting arguments about the entanglement of Western desire for both cargo and cults with these Melanesian visions of how to create a prosperous future for themselves.